2019
DOI: 10.1016/j.fuel.2018.07.053
|View full text |Cite
|
Sign up to set email alerts
|

Steam gasification behavior of tropical agrowaste: A new modeling approach based on the inorganic composition

Abstract: The steam gasification and co-gasification reactivity and kinetics of coconut shells, oil palm shells and bamboo guadua were studied from an isothermal thermogravimetric analysis, with temperatures ranging from 750°C to 900°C, and steam partial pressures from 3 to 10 kPa. In the analyzed experimental range, inorganics were identified as the most influential parameter in biomass reactivity and kinetics. Accordingly, a new modeling approach is proposed to predict the gasification behavior of lignocellulosic agro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 43 publications
3
23
0
Order By: Relevance
“…For the three feedstocks, the recovered char at the end of the gasification process was reduced with the increase of the steam fraction in the gasifying agent, the temperature, and the gasification time. The impact of these parameters on the gasification behavior of CS, BG, and OPS was analyzed in a previous work at a thermogravimetric scale 18 and is in accordance with the results obtained in this study. More specifically, higher gasification temperatures and steam quantities are related to higher reactivities and then to higher carbon conversions and lower char yields.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…For the three feedstocks, the recovered char at the end of the gasification process was reduced with the increase of the steam fraction in the gasifying agent, the temperature, and the gasification time. The impact of these parameters on the gasification behavior of CS, BG, and OPS was analyzed in a previous work at a thermogravimetric scale 18 and is in accordance with the results obtained in this study. More specifically, higher gasification temperatures and steam quantities are related to higher reactivities and then to higher carbon conversions and lower char yields.…”
Section: Resultssupporting
confidence: 90%
“…The chars obtained from the steam gasification of oil palm shells (OPS), coconut shells (CS), and bamboo guadua (BG) were characterized and analyzed in this study. The chemical organic and inorganic composition of the raw materials were determined according to the standards of solid biofuels, detailed in a previous work, 18,22 and are summarized in Table 1. 2.2. Gasification Experimental Setup.…”
Section: Methodsmentioning
confidence: 99%
“…Biomass content in inorganic elements, especially potassium, silicon and phosphorous, is known to impact solid yield in gasification reactions at higher temperatures (above 800 • C) [32,33]. However, this impact is still open to discussion in the torrefaction temperature range [17,[34][35][36].…”
Section: Influence Of the Inorganic Element Contentmentioning
confidence: 99%
“…These studies concluded that CO 2 influence on solid transformation through torrefaction was existent but limited [29]. The presence of water in the torrefaction atmosphere was studied in 'wet torrefaction' or hydrothermal carbonization, where biomass typically reacts between 180 and 260 • C at a pressure of several tens of bars [30,31], as well as in gasification, at temperatures from 800 • C. In gasification, potassium (K) was reported as a catalyst of solid mass loss, while phosphorous (P) and silicon (Si) seem to inhibit gasification reactions [32,33]. These conditions of temperature and pressure drastically differ from those encountered in typical torrefaction, and thus, clearly prevent the drawing of conclusions that are valid for this process [17,[34][35][36] The significant water vapor content of the torrefaction gases may impact biomass solid degradation kinetics in torrefaction, and thus, needs to be considered so as to optimize the process at an industrial scale.…”
mentioning
confidence: 99%
“…Steam gasification biochars obtained from three tropical lignocellulosic agrowastes were characterized and analyzed in this study. Coconut shells (CS), bamboo guadua (BG), and oil palm shells (OPS) were selected as raw materials, considering their different macromolecular and inorganic composition, determined according to the standards of solid biofuels (detailed in previous works [29,30]), and summarized in Table 1.…”
Section: Raw Materialsmentioning
confidence: 99%